2017
DOI: 10.4077/cjp.2017.baf450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Administration of Adipokinetic Hormone on Depression, Anxiety, Pain, Locomotion and Memory in Mice

Abstract: The neurosecretory cells in the corpus cardiacum of insects synthesize a set of hormones that are called adipokinetic, hypertrehalosemic or hyperprolinemic depending on the insect in question. They are the Adipokinetic Hormone/Red Pigment-Concentrating Hormone (AKH/RPCH) family of peptides. The present study investigated the effects of acute administration of Locusta Migratoria (Locmi-AKHII) and Anax Imperator (Anaim-AKH) on depression, anxiety, pain (analgesy), locomotion and memory in mice in forced swimming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…In the AAPA test, we administered the drugs subchronically and observed no memory deficit in naive animals. Similarly, AKH caused no memory deterioration in the passive avoidance test after acute administration in our recent study . This supports that the AKH/RPCH family of peptides do not cause psychosis or memory deterioration in naive animals.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the AAPA test, we administered the drugs subchronically and observed no memory deficit in naive animals. Similarly, AKH caused no memory deterioration in the passive avoidance test after acute administration in our recent study . This supports that the AKH/RPCH family of peptides do not cause psychosis or memory deterioration in naive animals.…”
Section: Discussionsupporting
confidence: 88%
“…For example, in the AAPA test, Ani‐AKH reversed hyperlocomotion caused by MK‐801 while Lia‐AKH had a partial effect, while Pht‐HrTH increased the total distance moved when combined with MK‐801. In our recent studies, we found that when these hormones were administered chronically, they all increased locomotion , while Ani‐AKH diminished locomotion at the 4‐mg/kg dose when administered acutely . In the AAPA test, we administered the drugs subchronically and Ani‐AKH decreased MK‐801‐induced hyperlocomotion, a finding that corresponded with our previous study findings .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations